A method for fault diagnosis of power system of carrier rocket engine based on linear-quadratic receding time-domain algorithm. (March 2022) - Zhang, Tong; Zhao, Xiaohan; Hu, Renyi; Fu, Wenxing
The article studies the fault diagnosis of the first-stage power system of a carrier rocket made up of multiple engines. It establishes the simplified 6-DOF nonlinear model and uses the extended Kalman filter to generate residual errors. The quadratic receding time-domain algorithm is used to detect faults, and estimation vector fault characteristics are used to estimate precisely the thrust loss degree. Faults are located with the direction of abrupt change in overload fault. The simulation results show that the method can quickly detect engine faults, estimate the thrust loss degree with fault estimation values, and locate precisely the serial number of the faulty engine of the power system made up of multiple engines. The method boosts the development of the online health management technology of the power system of a carrier rocket.